Human resource development : foundations, process, conteexts - 285721 Gibb, Stephen (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan)
"The newest edition of this highly successfuly book provides a complete and integrated introduction to the processes, practices and perspectives of HRD in the workplace from a theory and practice perspective. Various aspects of HRD at work are explored through case studies, encouraging the student to link the practicalities of HRD with academic analysis"--